The Effectiveness of Peace Education on Students' Academic Competence and Positive Orientation Towards School - Leila Zamani kokhaloo; Mojgan Sepah mansor; Khadijeh Abolmaali Alhosseini (پژوهش در نظام‌های آموزشی, 2021)
The aim of this study was to investigate the effectiveness of peace education, academic competence and positive orientation of students towards school in a quasi-experimental method with a pretest-posttest design considering the control group and one-month followup. Its statistical population was female students of the first year of high school in the 19th district of Tehran (5901 people) who were studying in the schools of this region in the academic year 1399-1398. Sample size:40 students of different levels of education in the first year of high school are interested in cooperating in the study and have been selected by purposive sampling method. Data collection tools were ACES DePerna & Eliot (1999) Academic Competency Assessment Questionnaire Abolmaali & Aahmadi (2017) Positive Orientation Questionnaire.After performing the pre-test, the experimental group received peace training in 8 sessions of 90 minutes in 8 consecutive weeks and the control group did not receive any training in this field. For data analysis,the method of analysis of variance was measured.Repeatedly used.The results showed that peace education had a positive effect on the development of students 'academic competence in the components (academic skills and academic empowerment) and students' positive orientation in the component of attitudes toward classmates and this effect remained stable after the followup phase (P <0.01). The results of this study indicate the need to learn how to live together.Peace education, by influencing the skills of academic enablers as well as creating a positive attitude towards classmates,promotes academic competence and improves relationships between students in the school.